2023
DOI: 10.1371/journal.ppat.1010889
|View full text |Cite
|
Sign up to set email alerts
|

A special satellite-like RNA of a novel hypovirus from Pestalotiopsis fici broadens the definition of fungal satellite

Abstract: Satellites associated with plant or animal viruses have been largely detected and characterized, while those from mycoviruses together with their roles remain far less determined. Three dsRNA segments (dsRNA 1 to 3 termed according to their decreasing sizes) were identified in a strain of phytopathogenic fungus Pestalotiopsis fici AH1-1 isolated from a tea leaf. The complete sequences of dsRNAs 1 to 3, with the sizes of 10316, 5511, and 631 bp, were determined by random cloning together with a RACE protocol. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
0
1
0
Order By: Relevance
“…Notably, the effects of hypovirus infection on their host varied. For example, CHV4/SR2, FgHV1, VcHV1, and Pestalotiopsis fici hypovirus 1 (PfHV1) had no significant effect on their hosts [41,43,66,67]. By contrast, CHV1/EP713, CHV2/NB58, CHV3/GH2, and FgHV2 were associated with the hypovirulence of their host [42,[68][69][70][71].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Notably, the effects of hypovirus infection on their host varied. For example, CHV4/SR2, FgHV1, VcHV1, and Pestalotiopsis fici hypovirus 1 (PfHV1) had no significant effect on their hosts [41,43,66,67]. By contrast, CHV1/EP713, CHV2/NB58, CHV3/GH2, and FgHV2 were associated with the hypovirulence of their host [42,[68][69][70][71].…”
Section: Discussionmentioning
confidence: 98%
“…However, the infection of BcHV1 alone without the satellite RNA significantly reduced virulence without affecting mycelial growth [46]. A recent study showed that satellite-like RNA could negatively regulate the expression of helper virus PfHV1 [66]. Notably, BdHV1/SXD111 had no evident impact on the morphologies and virulence of the host fungus.…”
Section: Discussionmentioning
confidence: 98%
“…Except for a limited number of mycovirus-associated satRNAs [15][16][17], the majority of satRNAs are associated with plant-infecting positive sense (+) RNA viruses [14], which represent the largest category of plant viruses and pose significant threats to global agriculture. Upon infection, these (+) RNA viruses release their genomic RNAs to produce viral replication proteins.…”
Section: Introductionmentioning
confidence: 99%